PERAN EKONOMI SYARIAH DALAM MEMBANGUN KETAHANAN EKONOMI DESA DI ERA DIGITAL - Mariatul Qibtiyah (Wasīlah: Journal Of Sharia Sciences, 2026)
Rural economic resilience has become an important issue amid increasing community vulnerability caused by limited access to capital, low financial literacy, weak market access, and digital risks. Islamic economics has strategic potential to address these problems because it promotes the principles of justice, mutual assistance, risk sharing, real-sector empowerment, and protection for vulnerable groups. This study aims to analyze the role of Islamic economics in strengthening rural economic resilience in the digital era, particularly through Islamic financing, Islamic social finance, social capital, financial literacy, and the use of digital technology. This research employed a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews, observation, and documentation involving micro, small, and medium enterprise actors, village-owned enterprise managers, religious leaders, socio-religious institutions, and rural community members. The data were analyzed thematically to identify patterns, dynamics, and substantive meanings of Islamic economic practices at the village level. The findings indicate that Islamic economics functions not only as a financing instrument but also as an empowerment ecosystem that connects zakat, infaq, sadaqah, waqf, cooperatives, Islamic microfinance institutions, village-owned enterprises, MSMEs, mosques, Islamic boarding schools, and digital technology. The novelty of this study lies in positioning Islamic economics as an ecosystem of rural economic resilience rather than merely as a product of financial institutions. The implications of this research highlight the need to integrate Islamic economic policies, financial literacy, MSME digitalization, and the strengthening of local institutions. Scientifically, this study contributes to the development of Islamic social finance, financial inclusion, rural resilience, and digital transformation studies within the context of rural development.